Rethinking methodologies in critical terrorism studies: a mixed-method randomised control trial study on community reintegration of former Boko Haram members in Nigeria - Ike, Tarela Juliet (Methodologies in critical terrorism studies, 2024)
Critical Terrorism Studies (CTS) are limited in terms of their engagement with robust interdisciplinary and evidence-based methodologies. So far, qualitative studies dominate research on CTS, including the limited use of statistical analysis or methodologies underpinned by experimental design. This chapter argues that the limited use of experimental design limits what can be said and claimed as effective within the context of CTS, including counterterrorism literature. This chapter highlights the need to draw on interdisciplinarity regarding how we engage with CTS as it strengthens the existing knowledge base, promotes methodological rigour and fosters replication. Drawing on a case study of improving community reintegration of former Boko Haram defectors and their families into society in Nigeria, the chapter aims to show how using a mixed-methods experimental design that fuses psycho-legal intervention and frameworks from CTS could help provide evidence-based recommendations that can be instrumental in the reintegration of these persons into society. The chapter concludes that through interdisciplinary and empirically rigorous approaches, researchers can open up spaces for innovation and replication that strengthen the discipline’s knowledge base.